Effects of in vitro digestion–fermentation over global antioxidant response and short chain fatty acid production of beet waste extracts in Ca(II)– alginate beads - Aguirre Calvo, Tatiana Rocio (2020)
The aim of the present work was to analyze the effect of in vitro gastrointestinal digestion-fermentation on antioxidant capacity, total phenols and production of short chain fatty acids (SCFAs) from biocompounds derived from beet waste (leaf and stem) encapsulated in different formulations of Ca(ii)-alginate beads. The encapsulated systems presented higher antioxidant capacity in different phases (digested and fermented) than the extracts without encapsulation, making Ca(ii)-alginate beads a suitable delivery vehicle. Levels of total phenolic compounds and antioxidant capacity of the fermented fraction were up to ten times higher than those of the digested fraction, boosted by the contribution of bioactive compounds from the by-product of beet as well as by sugars and biopolymers. Among the formulations used, those that had excipients (sugars and/or biopolymers) presented a better overall antioxidant response than the beads with just alginate. Guar gum and sucrose lead to a promising enhancement of Ca(ii)-alginate beads not only for preservation and protection but also in terms of stability under in vitro digestion-fermentation and production of SCFAs.